Numerical Investigation on The Open Water Characteristics of B-Series Propeller - Andik Machfudin; A.A.B. Dinariyana; Dian Purnama Sari (Department of Naval Architecture - Diponegoro University, 2023)
Computer fluid dynamics (CFD) has been increasingly popular in the present day attributable to the reasonably accurate results, time and money savings, and ease of use for calculating the open water characteristics of the propeller. This paper presents the results of a computational evaluation of propeller open water characteristics based on various advanced velocities and advanced coefficients. KT, KQ, and ƞ are verified to get optimal performance study results. Research on mesh convergence is conducted with an advance coefficient of J = 0.6 with investigate three meshes coarse, medium, and fine. The impacts of mesh density and mesh production are examined for the purpose of increasing the accuracy of the numerical findings. The B-series propeller is used to verify and validate the accuracy of case studies. Obtained results show that the CFD result is well in agreement with the experimental result.